The Role of Judicial Independence in Upholding Civil Rights : Challenges and Opportunities - Muhamad Firdaus; Eka Putra Nur Hidayat (International Forum of Researchers and Lecturers, 2024)
Judicial independence is a cornerstone of democratic societies, crucial for upholding civil rights and ensuring justice. This article explores the relationship between judicial independence and the protection of civil rights, highlighting both challenges and opportunities. Through case studies and analysis, it identifies factors that influence judicial autonomy, such as political interference, resource allocation, and legal safeguards. The study concludes by offering recommendations to strengthen judicial independence and, consequently, enhance civil rights protection in legal systems worldwide.